Pengaruh Konsentrasi Maltodekstrin dan Glukomanan Terhadap Karakteristik Serbuk Minuman Instan Daun Jeruju (Acanthus ilicifolius L.) - Padangratha, Ida Ayu Ambararacmi; Puspawati, Gusti Ayu Kadek Diah; Putra, I Gede Arie Mahendra (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2025)
Jeruju leaves are a type of mangrove plant that contains phenolic compounds and have been developed as a powdered instant drink using maltodextrin encapsulant. Maltodextrin has poor viscosity so it can be combined with encapsulants like glucomannan. The concentration between maltodextrin and glucomannan to achieve product with the best characteristics can be affected by the material used. This research aimed to know the effects of maltodextrin and glucomannan concentration on the characteristics of jeruju leaves instant drink powder, also to know the right maltodextrin and glucomannan concentration to achieve a product with the best characteristics. This research used Completely Randomized Design Factorial with two factors: 1) maltodextrin concentration (10%; 20%) and 2) glucomannan concentration (0%; 0.5%; 0.75%; 1%), the repetition was done 2 times. Data was analyzed using Analysis of Variance, if treatment affected the observed variable, it will be continued with Duncan Multiple Range Test. Results showed that the interaction between maltodextrin and glucomannan has real impact on total phenolic compound, encapsulation efficiency, and antioxidant activity. Each maltodextrin and glucomannan concentration has real impact on yield, meanwhile maltodextrin concentration individually has real impact on ash content, water content, and dissolving time. The concentration of  20% maltodextrin and 0.75% glucomannan resulted in jeruju leaves instant drink powder with the best characteristics: yield 18.48%, water content 3.99%, ash content 1.54%, total phenolic compound 9.19 mg GAE/100g, encapsulation efficiency 84.09%, antioxidant activity 66.38%, dissolving time of 2.54 minutes, color, aroma, taste, and overall acceptance showed slightly liked score.